Some Insights on Kerr Lensing Effects - Aït-Ameur, Kamel; Hasnaoui, Abdelkrim (Photonics, 2025)
The research on high-order transverse modes in lasers was largely abandoned a few years after the invention of the laser in 1960. The main reason for this was that high-order beams are more divergent and less bright than the Gaussian beam. In the present paper, we showed that the behaviour of LGp0 beams faced to the optical Kerr effect (OKE) varies considerably depending on the mode order (p = 0 or p≥1). We focused our attention on the properties of LG00 and LG10 beams when subject to OKE, and we found that the LG10 beam keeps its focusability much better than the LG00 beam. This property has at least two applications concerning first the conception of high-intensity laser chains not based on a Gaussian beam but on an LG10 beam and second, the use of an LG10 beam instead of the usual Gaussian beam which can reduce drastically the protection of optical limiters based on OKE; this constitutes a counter-measure against such limiters.